A spatially explicit approach to assess the suitability for rice cultivation in an inland valley in central Benin - Danvi, A.; Jütten, T.; Giertz, S.; Zwart, Sander J.; Diekkrüger, B.A (Elsevier, 2016)
The selection of optimal areas for specific cultivation systems is an important step in achieving increased, sustainable rice production in Benin. This study aims to determine suitable areas for rice production in the inland valley of Tossahou using a GIS-based approach that evaluates and combines biophysical factors such as climate, hydrology, soil and landscape, following the FAO parameter method and guidelines for land evaluation. Soil and landscape suitability was assessed for three different rice cultivation systems: rainfed bunded (RB), cultivation under natural flooding (NF), and irrigated cultivation (RI). The results show that in the inland valley (mostly including the hydromorphic zones and the valley bottom) 52% of the area is suitable for irrigated cultivation, 18% for cultivation under natural flood and 1.2% for rainfed bunded rice. Precipitation and temperature were limiting factors for all cultivation systems. Flooding was the most limiting factor for NF while RI and RB were mostly limited by steep slopes and soil texture respectively. As a first attempt in Benin, this study can play an important role in achieving optimised rice production in inland valleys, and additional studies including socio-economic aspects, carried out in the same area, or in areas under similar conditions, are relevant to close the yield gap and improve the selection approach.